WITHDRAWN: Vaginal fluid IL-6 concentrations as a point-of-care test is of value in women with preterm PROM - Musilova, Ivana; Bestvina, Tomas; Hudeckova, Martina; Michalec, Igor; Cobo, Teresa; Jacobsson, Bo; Kacerovsky, Marian (American journal of obstetrics and gynecology, 2016)
The Publisher regrets that this article is an accidental duplication of an article that has already been published, http://dx.doi.org/10.1016/j.ajog.2016.07.001 . The duplicate article has therefore been withdrawn. The full Elsevier Policy on Article Withdrawal can be found at https://www.elsevier.com/about/our-business/policies/article-withdrawal
Keywords: biomarkers; interleukin; microbial invasion of the amniotic cavity; amniocentesis; amniotic fluid; noninvasive procedure; rapid test; MIAC; preterm; intra-amniotic inflammation; lateral flow-based immunoassay; cytokine